2016
DOI: 10.1111/codi.13329
|View full text |Cite
|
Sign up to set email alerts
|

Does percutaneous tibial nerve stimulation improve global pelvic function in women with faecal incontinence?

Abstract: For patients presenting with faecal incontinence, PTNS appears to have a positive effect on bowel related function in approximately two-thirds of patients. However, for treatment responders, improvement appears to relate mainly to improvement in bowel related function rather than a global pelvic floor effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Posterior Tibial Nerve Stimulation (PTNS) is another option that recent studies have indicated its high effectiveness (Bondurri, Maffioli, & Danelli, 2015;de Groat & Tai, 2015;Edenfield, Amundsen, Wu, Levin, & Siddiqui, 2015;Giani & Musco 2015;Grossi et al, 2015;Gupta, Ehlert, Sirls, & Peters, 2015;Jiménez-Toscano et al, 2015;Kelly, Radley, & Brown, 2016;Lecompte, Hery, Guys, & Louis-Borrione, 2015;Lopez-Delgado et al, 2014;Marti & Maurus, 2014;Moya et al, 2016;Pena Ros et al, 2016;Sucar-Romero, Escobar-del Barco, Rodriguez-Colorado, & Gorbea-Chavez, 2014;Wexner, 2015). Although there is still an ongoing controversy regarding PTNS in FI treatment, PTNS is low cost and easy to operate without anesthesia (Hotouras et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior Tibial Nerve Stimulation (PTNS) is another option that recent studies have indicated its high effectiveness (Bondurri, Maffioli, & Danelli, 2015;de Groat & Tai, 2015;Edenfield, Amundsen, Wu, Levin, & Siddiqui, 2015;Giani & Musco 2015;Grossi et al, 2015;Gupta, Ehlert, Sirls, & Peters, 2015;Jiménez-Toscano et al, 2015;Kelly, Radley, & Brown, 2016;Lecompte, Hery, Guys, & Louis-Borrione, 2015;Lopez-Delgado et al, 2014;Marti & Maurus, 2014;Moya et al, 2016;Pena Ros et al, 2016;Sucar-Romero, Escobar-del Barco, Rodriguez-Colorado, & Gorbea-Chavez, 2014;Wexner, 2015). Although there is still an ongoing controversy regarding PTNS in FI treatment, PTNS is low cost and easy to operate without anesthesia (Hotouras et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez y equipo notificaron mejoría significativa a los 12 meses del inicio del tratamiento. 1,3,5,[9][10][11][17][18][19][20]22,23,[26][27][28][29][30][31][32][33][34] Otro punto que se debate en la literatura es la realización de estudios manométricos comparativos posterior a la neuromodulación. Por esto decidimos evaluar parámetros manométricos (presión de reposo y contracción) antes y después del tratamiento.…”
Section: Escala De Wexnerunclassified
“…On top of being a major cause chronic pelvic pain, endometriosis or its treatment is intimately related to bladder, bowel and sexual dysfunction. Neuromodulation has been shown to be effective at improving all these aspects of pelvic floor function – pain, bowel, bladder and sexual function – which potentially makes it particularly useful in the adjuvant treatment of endometriosis (23). These indications will be further reviewed in the following paragraphs.…”
Section: Role Of Neuromodulation In the Treatment Of Endometriosismentioning
confidence: 99%